As políticas públicas para a cultura nos municípios de Santo Ângelo e São Luiz Gonzaga, no Rio Grande do Sul: uma análise a partir da percepção dos artistas e dos gestores municipais - Fontana, Jerson Vicente (2017)
The following master’s dissertation approaches public policies on the art fields at the municipalities of Santo Ângelo (RS) and São Luiz Gonzaga (RS), aiming to comprehend its impacts on the artists’ lifes and on their artistic production. Therefore, municipal, state and federal legislation data were utilized, withdrawn from Court State Account of Rio Grande do Sul (TCE-RS) and from bibliographic search. In addition, qualitative interviews were hold with public managers and artists of the researched city. It was pointed, by the study conclusion: that the artists do not consider relevant the public investments for the development of its activities; there are disparities between the perceptions of the artists and public managers on what concerns the arts and its fomentation by means of public policies; that the allocation of invested resources by the arts sector of the municipalities present substantial dissonance in regards to described priorities by local artists.